(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The Uzbek people have a long history, from the past until the second half of the XIX century, they were referred to by Turkic, Sart, Chigatay and finally Uzbek terms. The process of finding the content of the Uzbek language.